Farm Diversification and Food and Nutrition Security in Bangladesh: Empirical Evidence from a Nationally Representative Household Panel Data. - Islam, Saiful. (Tufts University. Tisch Library., 2017)
This presentation examines data from nationally representative household panel data looking at farm production diversity, diet diverstiy, income, and market access.